The Effect of Concept Map on Studentâs Learning outcome for Ecosystem in Grade Tensma Islam Al Ulum Terpadu Medan - Syamsiah, Syamsiah (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Concept maps are tools for organizing and representing knowledge. They include concepts, usually enclosed in circles or boxes of some type, and relationships between concepts or propositions, (indicated by a connecting line and linking word) between two concepts. Linking words on the line specify the relationship between the two concepts.This quasi experiment research aim to investigate the effect of technique concept map on the student learning outcome in ecosystem topic. The research conduct in grade X SMA ISLAM AL ULUM TERPADU Medan. The population of this research are 46 students and sample are total sampling consisting 46 students and samples are total sampling consisting 23 students, as an experimental class (X-B) And 23 Students of control class (X-A). 30 items of multiple choice test were used and validated before they were applied. The result shows that pretest in experimental and control class are (59.13 _+ 12.12) and (59.34 +- 14.16) t test reveals t cal -0.18 t table (1.687) : Î± =0.05. Pretest has no significant effect in the students preliminary knowledge. In the contrary, past test show different result ( experimental class = 76.08 +_ 10.65; control class 67.60 +_ 8.90 ) . T test reveals that t count (2.98) > t table (1.678). This finding states that treatments has significant effect on students learning outcomes in biology. It advisable that technique concept map is in corporate in the learning process especially in teaching biology.